PERENCANAAN KEUANGAN SYARIAH BAGI KELUARGA PADA DESA BANYU ASIH, KECAMATAN CIGUDEG, KABUPATEN BOGOR - Anwar, Miftakhul; Melinasari, Susi; Rizqulloh, Farras Aufa (Jurnal Pengabdian Kepada Masyarakat Perbankan Syariah: Program Studi Perbankan Syariah., 2025)
This community service aims to overcome the problems that exist in Banyu Asih village. The subjects of this community service are the people of Banyu Asih Village, Cigudeg District, Bogor Regency, West Java Province. In this community service, activities are carried out based on the Participatory Action Research (PAR) approach method. The result of this community service is to produce a stable family economy. With this community service, it can be concluded that with the implementation of sharia financial planning, many families can now manage their finances better, reduce dependence on debt, and increase savings for future needs. As a result, people not only experience better financial stability but also create a social environment that is more harmonious and mutually supportive in achieving common economic goals